Extraosseous chondroma of anterior neck in pediatric patient. Issue 8 (August 2015) - Ikeda, Ryoukichi; Tateda, Masaru; Okoshi, Akira; Morita, Shinkichi; Hashimoto, Sho
Abstract Extraosseous chondroma (EC) is uncommon soft tissue tumor composed of hyaline cartilage without connection to bone or periosteum. The frequent sites of EC are the hands and feet and rarely reported in the pediatric population and anterior neck lesion. We present an extremely rare case of anterior neck mass in a 5-year-old male who underwent total resection, with the final diagnosis of EC. The review of the literature showed that all cases of EC in anterior neck lesion have been found in young age and preoperative diagnosis was difficult.